IODP Expedition 379 Magnetic remanence (spinner) ... - Gohl, Karsten; Wellner, Julia S.; Klaus, Adam; Bauersachs, Thorsten; Bohaty, Steven; Courtillat, Margot; Cowan, Ellen A.; De Lira Mota, Marcelo A.; Esteves, Mariana S.R.; Fegyveresi, John M.; Frederichs, Thomas; Gao, Liang; et al. (International Ocean Discovery Program, 2021)
Magnetic remanence was measured on discrete samples by an Agico JR-6A spinner magnetometer, first as natural remanent magnetization (NRM) and then after demagnetization or remagnetization steps were performed on the samples (e.g., alternating field [AF] demagnetization, thermal demagnetization [TD], or isothermal remanent magnetization [IRM]). ...